Market reactions to the servitization of product offerings - An event study on the software as a service model (Junior Management Science, 2018)
Servitization is transforming traditional manufacturing and product-oriented firms across industries in many ways. One of these transformations concerns the business models of firms that transform from selling products to provisioning products as a service with product-service systems (PSS). I analyze this form of servitization in the software industry, where the software as a service business model is becoming the standard for most start-ups as well as some big enterprises like Adobe and Autodesk. Event study methodology is applied to 359 software vendors’ announcements of new software as a service offerings between 2001 and 2015, analyzing how installed base, parallel business models and partnerships with external service providers influence the reaction in the stock price of the software vendors. I find that “as-a- service” business models are not perceived as a substitute but rather as a complement for perpetual product sales and that collaboration with specialized service providers for the delivery of the new offering is rewarded by the stock market. I explain the findings with organizational inertia within the software vendors’ organization as well as that of their customers. The findings are used to discuss how companies can manage the inertia by developing new product lines for the PSS model, offering perpetual product sales in parallel and cooperating with third party service providers for the service delivery. Servitization is transforming traditional manufacturing and product-oriented firms across industries in many ways. One of these transformations concerns the business models of firms that transform from selling products to provisioning products as a service with product-service systems (PSS). I analyze this form of servitization in the software industry, where the software as a service business model is becoming the standard for most start-ups as well as some big enterprises like Adobe and Autodesk. Event study methodology is applied to 359 software vendors’ announcements of new software as a service offerings between 2001 and 2015, analyzing how installed base, parallel business models and partnerships with external service providers influence the reaction in the stock price of the software vendors. I find that “as-a- service” business models are not perceived as a substitute but rather as a complement for perpetual product sales and that collaboration with specialized service providers for the delivery of the new offering is rewarded by the stock market. I explain the findings with organizational inertia within the software vendors’ organization as well as that of their customers. The findings are used to discuss how companies can manage the inertia by developing new product lines for the PSS model, offering perpetual product sales in parallel and cooperating with third party service providers for the service delivery. Keywords: SaaS, Software-as-a-Service, Servitization, Business model transformation, Stock markets